The implementation of an intensive second language reading intervention program for Arabic L1 learners of English as a foreign language. Issue 1 (18th March 2022) - Oakley, M. Joan; Kormos, Judit; McCray, Gareth
Abstract : The aim of this study was to investigate the effects of focused reading interventions on the eye movement patterns and reading scores of second language (L2) learners. We compared two groups of proficiency matched Arabic L2 learners before and after an intensive reading intervention program. Two classes received a barrage of reading interventions and two classes served as comparison groups. The intervention program consisted of textual enhancement, phonological awareness training, training in word recognition, spelling instruction and oral text reading fluency. Analysis of reading scores showed a significant improvement over time, but no significant impact of the intervention. Both the intervention and comparison groups showed improvement in their eye tracking measures, but no significant difference in gains between the intervention and the comparison groups was found. The study provides a building block for future studies using focused pedagogical interventions with this particular group of learners.